Optimasi dan Sintesis Selulosa Dialdehid Berbasis Limbah Tandan Kosong Kelapa Sawit - Sitinjak, Elvri Melliaty; Masmur, Indra; Shuwanto, Hardy; Dina, Sari Farah; Hutajulu, Poltak Evencus; Saragih, Gimelliya; Siahaan, Immanuel; Damanik, Fadhila Natania; Doloksaribu, Rahel Argana (Talenta Publisher (Universitas Sumatera Utara), 2025)
Empty Fruit Bunches of Oil Palm (EFB) represent one of the most problematic biomass wastes in Indonesia due to their massive volume, inefficient management, and underutilization of their chemical potential, leading to significant environmental, economic, and technical impacts. The degradation or processing of such large-scale waste generally requires a long period of time. This study focuses on converting the cellulose content in EFB into dialdehyde cellulose (DAC), which can be applied as a wet strength agent. The aim is to reduce EFB waste by isolating cellulose from EFB biomass and subsequently converting it into DAC, which can be utilized as a wet strength additive in paper or tissue products. The oxidation of EFB cellulose into DAC was optimized using sodium periodate (NaIO₄) as the oxidizing agent, with varying reaction times of 3, 6, and 9 hours. The synthesized DAC was qualitatively analyzed using the Fehling’s test and solubility observations, followed by functional group identification via FTIR and morphological characterization using SEM. Among the samples, DAC-6 exhibited the most optimal characteristics, with a degree of oxidation reaching 82.1% and a carbonyl content of 52.8%. FTIR analysis confirmed the presence of carbonyl functional groups in all DAC samples, indicating successful oxidation of hydroxyl groups in cellulose. DAC-6 showed the most prominent carbonyl absorption peak at a wavenumber of 1748 cm⁻¹.